Holotypes for three Caspian gastropods of the family Hydrobiidae tracked down: description and taxonomic interpretations - Anistratenko, Vitaliy V.; Sitnikova, Tatiana Ya.; Anistratenko, Olga Yu. (Zootaxa, 2021)
Type series of three nominal taxa of the hydrobiid gastropods inhabiting the Caspian Sea were traced recently in the uncatalogued part of the malacological collection of the Zoological Institute of Russian Academy of Sciences, Saint-Petersburg. Images of the holotypes and some paratypes of Pyrgula isseli Logvinenko & Starobogatov, 1969, P. sowinskyi Logvinenko & Starobogatov, 1969 and P. derzhavini Logvinenko & Starobogatov, 1969 are presented. The first two species belong to the genus Clathrocaspia (subfamily Caspiinae) and P. sowinskyi is considered a junior synonym of C. pallasii (Clessin & W. Dybowski in W. Dybowski, 1887). The attribution of the third species, P. derzhavini, to Laevicaspia (Pyrgulinae) is confirmed based on the newly discovered type material. Based on the additional information we update ecological data and distribution ranges of the species, provide comments on their nomenclature, systematic position and taxonomic rank.